EDUKASI PENCEGAHAN ANEMIA TERHADAP PENGETAHUAN DAN MOTIVASI DIET NUTRISI TINGGI ZAT BESI PADA IBU PRAKONSEPSI - Rini Nababan; Sarmauli Franshisca; Miftahul Jannah; Astri Yuni Fitri (Universitas Batam, 2024)
Preconception nutritional status is one of the factors that affect the condition of pregnancy and the well-being of the baby, if prevention is carried out at the time before pregnancy, the effect will be better. Deficiencies in macronutrient, vitamin and mineral intake are associated with the incidence of anemia because they influence each other in Hb synthesis. One of the policies to prevent anemia is the provision of blood supplement tablets to women of childbearing age and pregnant women. This study aims to determine the effect of anemia prevention education on knowledge and motivation of high iron nutrition diet in preconception mothers. This research method is quasy experimental design with “pretest and post-test without control group” research design. This research was conducted in the work area of the Niur Permai Health Center, Karimun Regency, the sample in this study were women of childbearing age who were planning pregnancy, totaling 30 people. The results of the study showed that the average knowledge of preconception mothers between before and after being given the treatment of Anemia Prevention Education is with a mean of 8.9053 obtained a p-value of 0.000 <0.05 and the average motivation of preconception mothers before and after being given Anemia Prevention Education is 0.000 where it can be seen that the p-value> 0.005 can be concluded that there is an influence and significant difference in the knowledge status and motivation of preconception mothers. It is recommended to provide adequate space and facilities for the implementation of education.